Awareness of HIV/AIDS among transportation staff linked to Dharan municipality, Sunsari, Nepal - Shrestha, Sharmila; Shah, T; Lamsal, S; Mandal, GN (Health Renaissance, 2017)
Background: Transportation workers are the high risk group for HIV/AIDS infection because they travel frequently; often engage in unsafe sex to reduce their loneliness. The UN predicts 68 million more deaths over the next twenty years if efforts on prevention are not increased. Objective: To assess the level of awareness and to find out association between awareness about HIV/AIDS and selected variables. Method: Cross sectional, descriptive study with sample of 197 staff (driver, conductor and helper) of buses and trucks of Dharan city. Purposive sampling technique was used with pretested semi structured questionnaire. Result: The median age of drivers was 28.5, conductor’s 28 and helper’s 21 years. Most of them (84.2%) were within the age group of 15-34 years. Majority stays (77.2%) less than a week away from home. Almost 93% had heard about HIV/AIDS. Still 55.8% & 32.5% believed HIV is transmitted by insect bite and having food together respectively. Eighty one percent believed that HIV/AIDS status of self should not be kept secret with sexual partner. More than (56.7%) had first sexual exposure at the age of 19 or below. Maximum (77.4%) had not used condom at first sexual intercourse. About 15.2% has sex with CSWs. Among them 93.3% were frequenting CSW for more than once. Forty percent had multi-partner. Conclusion: Staff of bus & truck of Dharan showed as the awareness level increased, risk taking behavior decreased and attitude became more positive among the transportation staff. Health Renaissance 2015;13 (3): 82-94